On geography and encounter: Bodies, borders, and difference - Wilson, Helen F. (Progress in human geography, 2017)
The notion of encounter has been used widely within work on urban diversity and socio-cultural difference, yet it remains under-theorized. This paper argues that ‘encounter’ is a conceptually charged construct that is worthy of sustained and critical attention. Drawing on a wide range of geographical interests, including animal geographies, urban diversity, postcolonialism, mobile geographies, and the more-than-human, it offers the first examination of how ‘encounter’ has been deployed across the discipline. By further tracing the historical links between geography and encounter, the paper contends that encounters are distinct genres of contact, and demonstrates why this matters for geographical thought, and how we think about bodies, borders, and difference.